Some new GWO variants for PV systems modelling - Srivastava, Simran; Hazra, Saumyadip; Agarwal, Shini; Sethi, Sauhardh; Ganguli, Souvik (International Journal of Psychosocial Rehabilitation, 2020)
Single Diode Model (SDM) is a popularly model used for the modelling of PV cells where five parameters are to be determined. This work accurately determines the five parameters of the SDM using meta-heuristic algorithm. Three equations have been considered for parameter extraction. The parameters of three widely used panels (KC200GT multi-crystal, MSX-60 poly-crystalline, and CS6K-280 M mono-crystalline) are extracted. The summation of the square of errors is used to define the error function. The Grey Wolf optimization (GWO) and its variants are being used. The values of the parameters and the error for all the three panels are compared for each algorithm. The results obtained are very promising and the error in the results is very less with EGWO proving out to be the best.